Author response: The human cough reflex has separate, distinct pathways. Issue 2 (6th February 2020) - Morice, Alyn H.; Kitt, Michael M.; Ford, Anthony P.; Tershakovec, Andrew M.; Wu, Wen-Chi; Brindle, Kayleigh; Thompson, Rachel; Thackray-Nocera, Susannah; Wright, Caroline
We thank J.A. Smith and co-workers for their interest in our paper [1]. Perhaps an even more ancient truth, that of William of Occam [2], should be applied to this discussion. The human cough reflex has separate, distinct pathways http://bit.ly/2PZgybq